INTEGRASI TEORI BELAJAR SOSIAL DALAM PENDIDIKAN ABAD 21 - Nabila Dayang Buana; Romlah Rahmatullah; Anisa Pamili; Winda Puspita; Riga Pranika Utami (Linggau Journal of Elementary School Education, 2026)
This study aims to analyze the integration of social learning theory in 21st-century education as an effort to improve the quality of adaptive and collaborative learning. The research employs a qualitative method with a library research approach. The research procedures include data collection from various sources such as books, scientific journals, and documents related to social learning theory and 21st-century educational practices. The data are analyzed using content analysis techniques through the processes of data reduction, data display, and conclusion drawing. The results show that the integration of social learning theory contributes significantly to the development of 21st-century skills, such as collaboration, communication, creativity, and critical thinking. In addition, the roles of modeling, observation, and social interaction are proven to enhance students’ learning motivation. The conclusion of this study emphasizes that the integrated implementation of social learning theory in learning can create an active, participatory, and relevant learning environment in accordance with contemporary demands.